1997
DOI: 10.1080/07391102.1997.10508155
|View full text |Cite
|
Sign up to set email alerts
|

The Role in Cell Binding of a β1-bend within the Triple Helical Region in Collagen αl(I) Chain: Structural and Biological Evidence for Conformational Tautomerism on Fiber Surface

Abstract: In its physiological solid state, type I collagen serves as a host for many types of cells. Only the molecules on fiber surface are available for interaction. In this interfacial environment, the conformation of a cell binding domain can be expected to fluctuate between the collagen fold and a distinctive non-collagen molecular marker for recognition and allosteric binding. If the cell binding domain can be localized in contiguous residues within the exposed half of a turn of the triple helix (approximately 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 50 publications
3
103
0
2
Order By: Relevance
“…While a number of earlier studies have highlighted the role of P15 to enhance bone formation, relatively few have focused on how it might be utilized to increase implant integration. 10,11,14,26,28,29 Previous studies by Bhatnagar et al, 11 demonstrated enhanced binding of cells to P15-coupled polyglycolate (PGA) fibers and mesh, compared to the PGA alone. Kubler et al, 30 demonstrated cells plated on P15/ABM formed multilayered sheets that clustered around the hydroxyapatite particles in contrast to cells plated on the other substrates which formed only monolayer sheets on the graft particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a number of earlier studies have highlighted the role of P15 to enhance bone formation, relatively few have focused on how it might be utilized to increase implant integration. 10,11,14,26,28,29 Previous studies by Bhatnagar et al, 11 demonstrated enhanced binding of cells to P15-coupled polyglycolate (PGA) fibers and mesh, compared to the PGA alone. Kubler et al, 30 demonstrated cells plated on P15/ABM formed multilayered sheets that clustered around the hydroxyapatite particles in contrast to cells plated on the other substrates which formed only monolayer sheets on the graft particles.…”
Section: Discussionmentioning
confidence: 99%
“…9 Both collagen and peptides DGEA and P15 are thought to bind integrin receptors stimulating osteoblastic differentiation and expression of the osteogenic phenotype. 10,11 P15 is the common name of a synthetic amino acid peptide (GTPGPQGIAGQRGVV) that is charecterstic of the cell-binding domain of human collagen type I protein. 10 Currently, it is used as a coating on the surface of anorganic bone material (ABM), where it promotes osteoblast differentiation and enhances cell adhesion, migration, and survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 TP508 is a thrombinderived peptide with wide specificity that causes angiogenesis, cytokine release, and appears to act through activation of an inflammatory response. 4,8 P-15 is a collagen-derived high-affinity cell-binding peptide 9 which increases cell attachment and modulates a number of gene products. 10,11 The 73-92 peptide corresponds to residues 73-92 of the knuckle epitope of BMP-2, 7 and while it activates alkaline phosphatase, it also blocks BMP-2 binding to its receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This product combines P-15, a synthetic 15-amino acid residue with a sequence identical to the cell-binding domain found on the a1(I) chain of Type-I collagen [3], onto an anorganic bovine-derived hydroxyapatite matrix (ABM) through a chemisorptive-coupling procedure [4]. The result is a complex that remains stable under physiologic conditions [5].…”
Section: Introductionmentioning
confidence: 99%